Modified HHT Method Usage for Vehicle Vibration Analysis in Time Domain - Juraj Gerlici; Tomas Lack (Communications - Scientific letters of the University of Zilina, 2008)
The paper deals with the analysis of vehicle vibrations in the time domain. The main aim is to modify the HHT-method for the solution of mechanical systems with nonlinear members. The modification enables the computation with the constant system computational matrix. This causes that the triangulation is to be performed once only and the nonlinear members affect only the right side of the algebraic equations system. This can dramatically decrease the time consumption of the computation. We used the method modified in this way for the dynamic analysis of the model with the parameters of the specimen “ERRI – vehicle” that was kinematically excited.